Pemanfaatan Jahe Gajah sebagai Produk Suplemen di Pekon Selapan, Kecamatan Pardasuka, Kabupaten Pringsewu - Zulpakor Oktoba; Afriyani Afriyani; Putu Ristyaning Ayu; Ari Irawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The community engagement team of the Faculty of Medicine, University of Lampung, conducted community services in the Jaya Lestari Pekon Selapan farmer group, Pardasuka District, Pringsewu Regency. The partner's problem is that elephant ginger (Zingiber officinale var. officinarum) still needs to be optimal in its use, limited to being harvested and then sold directly to collectors, and the selling price on the market is low. Farming groups have never used elephant ginger as a product. The activity aims to educate the public that elephant ginger can be utilized and developed to be processed into a product dosage form, which can add economic value by being made into an antioxidant health supplement product in the form of a pulvis preparation (powder). As well as increasing the capacity and welfare of the community through empowering the potential of the village resources. The method for implementing did through focus group discussions (FGD) included conveying theory through lectures, interactive discussion, and accompanying practical demonstrations in making elephant ginger powder products. The results of this activity show the high enthusiasm of farmer groups and women farmer groups (KWT) in producing elephant ginger powder products.